Effects of Freeze–Thaw Event on Microbial Community Dynamics During Red Clover Ensiling - Dong, Zhihao; Li, Junfeng; Chen, Lei; Wang, Siran; Shao, Tao (Frontiers in Microbiology, 2019)
Freezing damages in forages represents a major economic loss to agriculture. This study was conducted to investigate the effects of freeze–thaw (FT) event on microbial community dynamics of red clover silage. Results showed that the FT-treated material displayed higher proportions of Weissella and aerobic bacteria, while lower Pantoea and Enterobacter compared with the control material. The FT event promoted the development of Lactobacillus in silage microflora, inducing more intense lactic fermentation after an initial short lag. The aerobic bacteria were suppressed immediately after the onset of ensiling. Microbiomes of the two silages tended to be almost similar after 2 days of ensiling. However, a small number of aerobic bacteria tended to revitalize in the FT silage with prolonged ensiling time, indicated by apparent abundances of Acinetobacter and Pseudomonas at the end of ensiling. The results obtained here suggest that the FT event could promote the development of Lactobacillus during ensiling and the control of aerobe revitalization need to be concerned with silages made from the freeze-damaged forages.